ZNACZENIE PRAKTYK W ROZWIJANIU KOMPETENCJI NAUCZYCIELSKIEJ – PERSPEKTYWA PRAKTYKANTA I MENTORA - Siek-Piskozub, Teresa; Jankowska, Aleksandra (Neofilolog, 2019)
Teaching practice is an important stage in prospective foreign language teacher development. It is an opportunity for reflection on the teaching process as well as for (self) evaluation of one’s teaching competence. Trainees approaching their practicum should be prepared by their educational institutions for the challenges they may face in a real school context. In the article we report on two studies undertaken to obtain an insight into the practicum from the trainee perspective and from the school-based mentor perspective in the hope of identifying areas which require improvement. Descriptions of the design of the two studies and the analyses of their results are preceded by a discussion of the importance of reflection on foreign language teacher competence and the place of practicum in the development of competence.